Recurrent Betaherpetic Keratitis. Therapy Stages and Monitoring Methods of the Disease Dynamics - D. Yu. Maychuk; A. A. Tarkhanova; M. R. Taevere (Oftalʹmologiâ)
Purpose: to propose a stepbystep treatment regimen for betaherpetic keratitis with a method for monitoring the dynamics of the disease.Patients and methods. The study group included 40 patients (40 eyes). Each patient had a history of diagnosed unilateral recurrent acute or subacute keratitis, the etiology of the betaherpetic process was confirmed by laboratory diagnostic methods, confocal microscopy, based on the detection of specific “owl eye” cells. All subjects had previously received specific therapy with acyclovir. All patients underwent an ophthalmological examination, and then a twostage treatment regimen for keratitis was proposed. The main way to assess the dynamics of the disease, the presence of viral load and the need to intensify antiviral therapy was confocal microscopy data. The condition was assessed 1, 3, 6 and 12 months after the start of therapy. Results. As a result of the observation of a group of patients of 40 people, after 12 months, 33 patients achieved stable remission, 4 patients developed neurotrophic keratitis, and 3 patients had a relapse of betaherpetic keratitis. Recurrence of keratitis in 3 patients was detected within 2 to 4 months from the start of observation. Neurotrophic keratitis developed in 4 patients within 3 to 6 months from the start of observation.Conclusion. 1) The method of in vivo confocal microscopy can be used to monitor the dynamics of betaherpetic keratitis, based on the state of specific cells. 2) Therapy of betaherpetic keratitis requires the use of specific antiviral drugs with mandatory repeated preventive courses. 3) A history of herpesvirus infection requires assessment of the development of neurotrophic keratitis.